2022
DOI: 10.1101/2022.07.08.498895
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CNS myelination requires VAMP2/3-mediated membrane expansion in oligodendrocytes

Abstract: Myelin is required for rapid nerve signaling and is emerging as a key driver of CNS plasticity and disease. How myelin is built and remodeled remains a fundamental question of neurobiology. Central to myelination is the ability of oligodendrocytes to add vast amounts of new cell membrane, expanding their surface areas by many thousand-fold. However, how oligodendrocytes add new membrane to build or remodel myelin is unknown. Here, we show that CNS myelin membrane addition requires exocytosis mediated by the ve… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 109 publications
0
1
0
Order By: Relevance
“…While the molecular machinery regulating surface trafficking of metabolite transporters in OLs is still poorly understood, studies on adipocytes showed that VAMP2 and RAB5 family of GTPases are involved in GLUT4 glucose transporter trafficking [87][88][89] . Of note, VAMP2/3mediated exocytosis promotes membrane expansion in OLs and myelin formation during development 90 and VAMP3 regulates surface transport of the myelin protein PLP 91,92 . In Kir4.1 cKO mice, myelin sheath thickness and abundance of PLP in myelin was not affected, which is not surprising given that other transport-regulating proteins such as VAMP7 are also involved in PLP trafficking 91,92 .…”
Section: Discussionmentioning
confidence: 99%
“…While the molecular machinery regulating surface trafficking of metabolite transporters in OLs is still poorly understood, studies on adipocytes showed that VAMP2 and RAB5 family of GTPases are involved in GLUT4 glucose transporter trafficking [87][88][89] . Of note, VAMP2/3mediated exocytosis promotes membrane expansion in OLs and myelin formation during development 90 and VAMP3 regulates surface transport of the myelin protein PLP 91,92 . In Kir4.1 cKO mice, myelin sheath thickness and abundance of PLP in myelin was not affected, which is not surprising given that other transport-regulating proteins such as VAMP7 are also involved in PLP trafficking 91,92 .…”
Section: Discussionmentioning
confidence: 99%